ANALISIS DANA DEKONSENTRASI SEKTOR PENDIDIKAN DI PROVINSI SUMATERA BARAT - Putra, Gerry Hamdani (JURNAL PUNDI, 2020)
This research had a purpose to analyze deconcentration fund of education field in West Sumatera Province on 2011-2015. The type of analysis used is descriptive quantitative by collecting and analizyng the data of allocated deconcentration fund, Report on Budget Outcomes (RBO), Strategic Plan of Education Ministry, Accountability Report of Government’s Performance, program implementation, and relation with government in educational field. The result of the research showed that there are activities that were not accordance with the nature of deconcentration fund which is non-physical activity, such as in 2011 and 2012 there were still many physical activities such as building construction, laboratory equipment procurement, and rehabilitation of classroom and building of education office. The absorption of deconcentration fund would give a better affects for performance of education offices of West Sumatra Province. This could be seen from the total absorption of deconcentration funds that can increase the percentage of APK and APM which became the main indicator of the main programs in achieving performance.